ESTUDIO PALINOLÓGICO DE LA FORMACIÓN BAQUERÓ (CRETACICO), PROVINCIA DE SANTA CRUZ - IV - (Ameghiniana, 2013)
PALYNOLOGICAL STUDIES OF THE BAQUERó FORMATlON (CRETACEOUS), SANTA CRUZ PROVINCE,ARGENTINA,IV: In the present contribution al! trílete specíes having a cicatricose or canalículate sculpture are described. They are al! referred to the famuiy Schizaeaceae, genus Cicatricosisporites (including the types having appendices). Three of the species are known to occur in other taphofloras: Cicatricosisporites australiensis (Cookson) Potonié, C. hughesii Dettmann and C. cf. ethmos Delcourt and Sprumont. Four species are new: Cicatricosisporites ticoensis, C. baqueroensis, C. giganteus and C. annulatus. The variety of types indicates that the family Schizaeaceae was an important constituent of the Lower Cretaceous assemblages in Patagonia.